Dynamics of globalization, financial deepening and energy demand in Nigeria (Journal of Economic Research & Business Administration, 2021)
In recent times, globalization has raised issues on dynamics of economic globalization, financialdeepening and energy consumption. The present study has been an attempt to explore interlinks betweenthese variables using Toda-Yamamoto causal approach and ARDL bound cointegration approach.The results showed unidirectional causality run from globalization to financial deepening variables suchas credit to private sector and market capitalization. It is also observed that unidirectional causality runsfrom credit to private sector to energy consumption. No causal relationship runs from broad money supplyto globalization and energy consumption. The coefficient of globalization has a positive and statisticallysignificant effect on energy consumption for both short and long-run. The results also shows thatfinancial deepening has impact on energy consumption in Nigeria; the coefficients on the interactionbetween the globalization (GLS), broad money supply (BDS), credit to private sector (CPS) and marketcapitalization (MCP) are statistically significant at 5% level and with the positive sign in the short-runand negative sign in the long –run. Nigeria should develop its financial sector to enhance investment inenergy saving equipments to reduce fossil fuel consumption.Key words: Globalization, Financial development, Energy Consumption.